Problem Based Learning (PBL) Model: Its Effect in Improving Students’ Critical Thinking Skill - Aini, Dora; Latifah, Sri; Hamid, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on the critical thinking skills of 7th-grade students of SMP Negeri 34 Bandarlampung (Public Senior High School 34 Bandarlampung). This quasi-experiment involved 2 groups of students, totaling 28 students for the Experimental class and 26 students for the Control class. Data collection was obtained by using an essay test instrument which was presented in the pretest and posttest. Based on the research results, it is known that the posttest results of the experimental class are 78.82, and the results of the control class are 74.07. The data were then analyzed by independent sample t-test and obtained tcount (2.213) greater than ttable (2.007). The effectiveness of the Problem Based Learning (PBL) model was tested with the effect size test, the results showed a number of 0.2 with a low category. So, it can be concluded that the Problem Based Learning (PBL) model has an effect on increasing students’ critical thinking skills but with low effectiveness.